Patient–health care provider relationship: how can it impact on APS (Hughes' syndrome) adherence to treatment?. (October 2014) - Levy, RA; Signorelli, F
Adherence to treatment is fundamental for its success. It comprises compliance combined with persistency and should be constantly reassessed. This is true in all medical situations. In antiphospholipid syndrome (or Hughes' syndrome), in addition to taking the medication at the planned time so that its effect on blood can be assessed and the dose adjusted if necessary, all patients must incorporate healthy habits with a treatment that is lifelong and will be influenced by dietary changes and the use of many other medications. Following a regime for the treatment to be effective, and to avoid serious complications, often creates the sensation of 'living on a tightrope' for both the patients and the health care providers. Patient education along with constant monitoring using proper communication settings and tools are certain to improve adherence and outcomes.